A new species of Cardepia Hampson, 1905 (Lepidoptera: Noctuidae) from China - Gyulai, Peter; Saldaitis, Aidas (Zootaxa, 2014)
The genus Cardepia Hampson, 1905, which was revised by Hacker (1998), was reduced to 15 species after C. additamenda Hacker, 1998 was downgraded to a subspecies of C. hartigi Parenzan, 1981 (Hacker et al. 2002). Most of Cardepia have a trans-Palearctic distribution throughout the continental mountain steppe belt with most western Palearctic species being coastal-halophilous and Central Asian taxa being halophilous in the natron flats. Per Hacker (1998) only C. emmanueli Berio and C. mixta (Pagenstecher, 1907) are restricted to Eastern Africa. A detailed genitalic study of both sexes is needed to properly separate the species because all Cardepia, including numerous named subspecies, are very similar in their external features, wing pattern and genitalia. After the aforementioned exhaustive revisions of the genus it was somewhat unexpected that a new species was discovered by Alessandro Floriani in the Taklimakan desert (West China, Xinjiang province, Kashgar area), which is described as new herein.